PENINGKATAN MUTU PENDIDIKAN ANAK-ANAK DI KAMPUNG JAWA - KOTA BATAM - Wisnu Yuwono; Johny Budiman; Ria Bintan; Andrea Putri; Anna Isabella Lau; Jennifer Jennifer; Kendy Setiawan Hartono; Lily Indrawati; Meilita Meilita; Tiara Shinta; Theresia Desilva (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
This community service program aims to improve children's education programs in Kampung Jawa - Batam City, considering that school-age children are still not proficient in numeracy, which is caused by limited infrastructure and experts. The method used here is the method of teaching while playing, using a game that we have designed with the method of